الصعوبات التي تتعرض دارسي اللغة العربية لغير الناطقين بها - D.S., Muhammad Ridha; Nasution, Syamsarina (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2019)
The researh is aimed to analyze the Language was voices in which every people expressed their purposes, because these voices differ from one people to another, and from one environment to another, and god almighty has wisdom in this difference. As for anything other than his own, he cannot learn it alone, until he reads, speaks, and writes, but he must have a teacher, pronunciation, and experience. And he must understand the laws of this language in theory, then apply these laws to words and phrases from them, then pronounce these words and sentences كانت اللغة أصواتا يعبر بها كل قوم عن أغراضهم، فإن هذه الأصوات تختلف من شعب لآخر، ومن بيئة لأخرى، ولله تعالى حكمة في هذا الاختلاف.ومن الطبيعي أن يعلم الإنسان لغته التي نطق بها أبواه ومجتمعه ويتقنها ويعرف قواعدها وأحكامها الصوتية والصرفية والنحوية والدلالية. أما غير لغته فلا يمكن أن يتعلمها وحده، حتى يقرأ بها، ويتحدث، ويكتب، بل لا بد له من معلم، ونطق، وخبرة. وأنه لا بد له من فهم قوانين هذه اللغة فهما نظريا، ثم تطبيق هذه القوانين على كلمات وجمل منها، ثم نطق هذه الكلمات والجمل.